Across the space: applications of spatial transcriptomic technology in healthy and diseased muscle - Virtanen, Laura; D’Ercole, Chiara; Giordani, Lorenzo (Frontiers in Cell and Developmental Biology, 2025)
In recent years, spatial transcriptomics (ST) has emerged as a groundbreaking technology with the potential to transform and accelerate our understanding of cellular crosstalk. While single-cell approaches have uncovered an unexpected level of cellular heterogeneity in both healthy and diseased tissues, they remain limited in their ability to capture cellular interactions in the native microenvironment. ST techniques bridge this gap by preserving anatomical information, enabling a direct investigation of spatially defined cellular interactions. This feature is particularly relevant in tissues such as skeletal muscle, where syncytial myofibers coexist with a heterogeneous set of interstitial cell populations. Spatial localization is a key factor during muscle regeneration, particularly as stem cell progression is driven by complex interactions between resident and recruited cell populations. Understanding these spatial dynamics is therefore critical to better characterize the fundamental mechanisms of muscle repair and identify aberrant signaling pathways of chronic injury or impaired regeneration. In this review, we will explore the various types of ST techniques, provide a brief summary of the available analytical tools, and highlight recent advancements in the skeletal muscle field enabled by the application of ST.